RNA sample preparation applied to gene expression profiling for the horse biological passport. Issue 9 (31st May 2017) - Bailly‐Chouriberry, Ludovic; Baudoin, Florent; Cormant, Florence; Glavieux, Yohan; Loup, Benoit; Garcia, Patrice; Popot, Marie‐Agnès; Bonnaire, Yves
Abstract : The improvement of doping control is an ongoing race. Techniques to fight doping are usually based on the direct detection of drugs or their metabolites by analytical methods such as chromatography hyphenated to mass spectrometry after ad hoc sample preparation. Nowadays, omic methods constitute an attractive development and advances have been achieved particularly by application of molecular biology tools for detection of anabolic androgenic steroids (AAS), erythropoiesis‐stimulating agent (ESA), or to control human growth hormone misuses. These interesting results across different animal species have suggested that modification of gene expression offers promising new methods of improving the window of detection of banned substances by targeting their effects on blood cell gene expression. In this context, the present study describes the possibility of using a modified version of the dedicated Human IVD ( in vitro Diagnostics) PAXgene® Blood RNA Kit for horse gene expression analysis in blood collected on PAXgene® tubes applied to the horse biological passport. The commercial kit was only approved for human blood samples and has required an optimization of specific technical requirements for equine blood samples. Improvements and recommendations were achieved for sample collection, storage and RNA extraction procedure. Following these developments, RNA yield and quality were demonstrated to be suitable for downstream gene expression analysis by qPCR techniques. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : The present study described the possibility to use a modified version of the dedicated human IVD PAXgene® Blood RNA Kit for gene expression analysis from horse blood collected on PAXgene® tubes applied to the horse biological passport.